Early Mars volcanic sulfur storage in the upper cryosphere and formation of transient SO2‐rich atmospheres during the Hesperian. (28th October 2016) - Schmidt, F.; Chassefière, E.; Tian, F.; Dartois, E.; Herri, J.‐M.; Mousis, O.
Abstract: In a previous paper (Chassefière et al.2013 ), we have shown that most volcanic sulfur released to the early Mars atmosphere could have been trapped in the upper cryosphere under the form of CO2 ‐SO2 clathrates. Huge amounts of sulfur, up to the equivalent of an 1 bar atmosphere of SO2, would have been stored in the Noachian upper cryosphere, then massively released to the atmosphere during the Hesperian due to rapidly decreasing CO2 pressure. It could have resulted in the formation of the large sulfate deposits observed mainly in Hesperian terrains, whereas no or little sulfates are found at the Noachian. In the present paper, we first clarify some aspects of our previous work. We discuss the possibility of a smaller cooling effect of sulfur particles, or even of a net warming effect. We point out the fact that CO2 ‐SO2 clathrates formed through a progressive enrichment of a pre‐existing reservoir of CO2 clathrates and discuss processes potentially involved in the slow formation of a SO2 ‐rich upper cryosphere. We show that episodes of sudden destabilization at the Hesperian may generate 1000 ppmv of SO2 in the atmosphere and contribute to maintaining the surface temperature above the water freezing point.